GAMBARAN STRES PADA MAHASISWA MAGANG DI JABODETABEK - Christine Elisabeth Widyachandra; Vivia Lee; Zamralita Zamralita; Venesia Venesia (Provitae: Jurnal Psikologi Pendidikan, 2023)
The number of students who continue to increase causes students to have to better prepare themselves so that they are ready to find work after graduating from college. One of the efforts to prepare students is to carry out internship activities. Internship activities aim to improve abilities and competencies through direct practice in the field. Internship activities can also improve the work readiness of students. However, students who carry out internships have greater demands than students in general. Unmanageable demands can cause students to experience stress. This study aims to look at the description of stress on intern students in Jabodetabek. This research was conducted using a descriptive quantitative method involving 100 apprentice student participants in Jabodetabek. This study used the Perceived Stress Scale (PSS) developed by Cohen et al. (1983). The results of this study were 71% of participants experienced moderate stress. The results of different tests conducted on the demographic data of gender and duration of apprenticeship showed values of 0.288 and 0.632. This value is greater than 0.05 which indicates that there is no significant difference between stress based on the demographic data. The factor that most caused the participants to experience stress was the occupational factor of 54.6%.